Calibrated relative sea levels constrain isostatic adjustment and ice history in northwest Greenland. (1st October 2022) - Glueder, Anna; Mix, Alan C.; Milne, Glenn A.; Reilly, Brendan T.; Clark, Jorie; Jakobsson, Martin; Mayer, Larry; Fallon, Stewart J.; Southon, John; Padman, June; Ross, Andrew; Cronin, Thomas; et al.
Abstract: Relative Sea Levels (RSLs) derived primarily from marine bivalves near Petermann Glacier, NW Greenland, constrain past regional ice-mass changes through glacial isostatic adjustment (GIA) modeling. Oxygen isotopes measured on bivalves corrected for shell-depth habitat and document changing meltwater input. Rapid RSL fall of up to 62 m/kyr indicates ice loss at or prior to ∼9 ka. Transition to an RSL stillstand starting at ∼6 ka reflects renewed ice-mass loading followed by further mass loss over the past few millennia. GIA simulations of rapid early RSL fall suggest a low regional upper-mantle viscosity. Early loss of grounded ice tracks atmospheric warming and pre-dates the eventual collapse of Petermann Glacier's floating ice tongue near ∼7 ka, suggesting grounding zone stabilization during early phases of deglaciation. We hypothesize mid-Holocene regrowth of regional ice caps in response to cooling and increased precipitation, following loss of the floating shelf ice. Remnants of these ice caps remain present but are now melting. Highlights: First use of stable isotopes in marine bivalves to correct subsurface habitat depths yielding sea-level index points. Rapid RSL fall in NW Greenland indicates rapid loss of terrestrial ice at or prior to 9 ka, predating collapse of Petermann Glacier's floating ice tongue. RSL stillstand in NW Greenland at ∼6 ka reflects renewed ice-mass loading in the neoglacial period. Implications: o Upper mantle viscosities in NW Greenland are lower than currently assumed in GIA models. o GIA response in NW Greenland reflects complex ice history and models should include the evolution of local ice caps.